Religion, law and governance in Malaysia - Bari, Abdul Aziz (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2010)
Although the number of provisions pertaining to Islam in the Federal Constitution of Malaysia is small, the substance of the religion practically permeates various aspects of governance in Malaysia. This seems to be quite natural given that Islam stands at the very heart of Malay civilisation and culture. Apart from this, the Malays form the majority of the country’s population. This would explain why – despite the fact that Malaysia belongs to the Westminster and Common Law systems of government and law – the Islamic character and essence of the polity remain visible. This is indeed interesting given that the country was governed by Europeans for several centuries – starting with the Portuguese who defeated the Sultanate of Malacca in 1511. As of now, the author argues that it would be possible to have a full-fledged Islamic system within the existing constitutional framework. According to him, the Malaysian experience could serve as an example of how a modern system of governance could co-exist with traditional Islamic values and systems. In recent years, the country has made significant progress in the field of Islamic banking and finance, as well as the systemisation of Islamic courts and education. Even the civil courts have eventually been able to strike a balance between the modern idea of liberty and Islamic notions of rights; something that was evident even in cases involving the question of apostasy. Interestingly enough, all of these achievements have been accomplished within the existing framework of the Constitution.